2022
DOI: 10.3390/microorganisms10071389
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Identification and Assessment of Bacterial Strains with Specific Probiotic Traits

Abstract: Early in the 1900s, it was proposed that health could be improved and senility delayed by manipulating gut microbiota with the host-friendly bacteria found in yogurt. Later, in 1990, the medical community reconsidered this idea and today probiotics represent a developed area of research with a billion-dollar global industry. As a result, in recent decades, increased attention has been paid to the isolation and characterization of novel probiotic bacteria from fermented foods and dairy products. Most of the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…The production of EPS facilitates gut colonization, thus representing a trait for probiotic bacterial evaluation ( 44 ). The EPS production influences the biochemical properties of the cell, including hydrophobicity and surface charge; EPS stabilizes microbial biofilm, enhancing bacterial adhesion and aggregation and increasing the tolerance to environmental stress ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The production of EPS facilitates gut colonization, thus representing a trait for probiotic bacterial evaluation ( 44 ). The EPS production influences the biochemical properties of the cell, including hydrophobicity and surface charge; EPS stabilizes microbial biofilm, enhancing bacterial adhesion and aggregation and increasing the tolerance to environmental stress ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that GSH-px activity was dramatically decreased by oxidative factors in mice, yet both modest and high doses of lactobacillus reversed such effect (Chen et al, 2005;Wu et al, 2021). Moreover, it was manifested that bacilli endospores are lysed during their transit through the gastrointestinal tract and release their intracellular antioxidative constituents, which in turn absorbed from the small intestine and flow to the circulation to extend the potential antioxidant effects (Torres-Maravilla et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another important biosynthetic capability in the genome was secondary bile acid biosynthesis by choloylglycine hydrolase (EC 3.5.1.24), an enzyme with possible appli-cations in hypercholesterolemia. Some probiotics show hypocholesterolemic effects in animal models due to reductions in lipid and cholesterol levels since BSH can deconjugate bile salts, inducing a de novo synthesis of conjugated salts at the expense of cholesterol, resulting in decreasing serum levels, alterations in energy, homeostasis and the excretion of larger amounts of free bile acids in feces, thus making BSH a clinically significant enzyme [40]. The BSH showed affinity to glycine and taurine secondary conjugates.…”
Section: Discussionmentioning
confidence: 99%